Projekt prywatnego ubezpieczenia na wypadek bezrobocia w polskich warunkach - Kawiński, Marcin (Private unemployment insurance - possibilities of omplementation in Poland, 2006)
Unemployment is considered to be very important issue in social policy. Very high unemployment rate noticed in Poland does not present all attributes of Polish unemployment. Some of the officially unemployed do not want to take up a (official) job, that is why the real unemployment rate is lower than the official one. Due to specific characteristics of Polish unemployment application of unemployment insurance (UI) requires very strict rules and carefully underwriting process. Although these difficulties it is possible to implement in Poland private supplementary UI, which may offer supplements to public system benefits. The simulations of private UI proves this statement. The results show much differentiation of premium because of level of education.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 186-196